2022
DOI: 10.3390/su14031594
|View full text |Cite
|
Sign up to set email alerts
|

Worming the Circular Economy for Biowaste and Plastics: Hermetia illucens, Tenebrio molitor, and Zophobas morio

Abstract: The negative impact of the modern-day lifestyle on the environment was aggravated during the COVID-19 pandemic through the increased use of single-use plastics from food take-aways to medical supplies. Similarly, the closure of food outlets and disrupted supply chains have also resulted in significant food wastage. As the pandemic rages on, the aggravation of increased waste becomes an increasingly urgent problem that threatens the biodiversity, ecosystems, and human health worldwide through pollution. While t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The degrading of polystyrene and polyurethane by both these species was associated with distinct microbiomes (a number of genera of bacteria were mentioned) although similar changes in chemical groups in plastics have been observed (Wang et al, 2022). Kuan et al (2022) showed that yellow mealworm, the superworm and Galleria mellonella utilise polystyrene and polyethylene for mineralisation as a carbon source. They identified some bacteria such as Pseudomonas aeruginosa in the superworm as the cause of polystyrene degradation.…”
Section: Biodegradation Of Plasticsmentioning
confidence: 84%
“…The degrading of polystyrene and polyurethane by both these species was associated with distinct microbiomes (a number of genera of bacteria were mentioned) although similar changes in chemical groups in plastics have been observed (Wang et al, 2022). Kuan et al (2022) showed that yellow mealworm, the superworm and Galleria mellonella utilise polystyrene and polyethylene for mineralisation as a carbon source. They identified some bacteria such as Pseudomonas aeruginosa in the superworm as the cause of polystyrene degradation.…”
Section: Biodegradation Of Plasticsmentioning
confidence: 84%
“…Gut microbes may facilitate the conversion of plastics such as polystyrene by mealworm species, such as T. molitor , Tenebrio obscurus , and Z. morio , but also by H. illucens (Kuan et al . 2022; Lou et al . 2021; Yang et al .…”
Section: Choosing Speciesmentioning
confidence: 99%
“…Superworm eats any type of feed even including plastic (Jiang et al, 2021;Luo et al, 2021;Yang et al, 2020). The astonishing thing about this animal is that it can survive without eating even for up to three weeks (Kuan et al, 2022). Of course, superworm can live well when given organic feed intake (van Broekhoven et al, 2015), especially feed with fibre above 5% (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%